2006
DOI: 10.1007/s11926-006-0069-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and magnetic resonance imaging in early rheumatoid arthritis: Recent advances

Abstract: Efficient methods for diagnosis, monitoring, and prognostication are essential in early rheumatoid arthritis. Data on the value of ultrasonography and MRI are accumulating rapidly, fueling their increasing use in early rheumatoid arthritis. This review focuses on recent advances in the clinical applications of these imaging modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Several comparative validation studies of MRI and US in adult rheumatology have been published 21,22,23,24 ; however, to the best of our knowledge, the 2 imaging modalities have …”
Section: Discussionmentioning
confidence: 99%
“…Several comparative validation studies of MRI and US in adult rheumatology have been published 21,22,23,24 ; however, to the best of our knowledge, the 2 imaging modalities have …”
Section: Discussionmentioning
confidence: 99%
“…This scheme is frequently supported by imaging techniques, such as radiography, ultrasound, and magnetic resonance imaging (MRI) [10, 11]. The latter facilitates an accurate diagnosis of early RA [12, 13], because it can be applied to confirm the presence of subclinical synovitis [14], to discover RA in clinical remission when there is no sign of swelling or tender joints [15] and to detect bone erosion with a higher sensitivity than plain radiography [16]. Furthermore, although it is not specific for RA, positron emission tomography (PET) with [ 18 F]2-fluoro-2-deoxy- d -glucose (FGD) can reveal arthritic lesions, because the advanced inflammatory processes are generally associated with an elevated energy conversion and, consequently, a higher glucose consumption.…”
Section: Introductionmentioning
confidence: 99%
“…25 Although plain radiographs remain essential for the initial assessment of patients with RA, several studies have suggested the use of ultrasonography and MRI as the imaging exams of choice for assessing early RA. 26 Enhanced MRI, in particular, is extremely sensitive, allowing the detection of areas de intraosseous infl ammation before overt erosions develop. Technical refi ning of those methods is being studied and shows promising results.…”
Section: Discussionmentioning
confidence: 99%